지방자치단체의 컨벤션센터 활성화 방안에 대한 구성원들의 인식 분석: 수익성 창출 요인을 중심으로 - 박정훈; Jung Hoon Park; 남창우; Chang Woo Nam (국가정책연구, 2016)
본 연구는 대구의 엑스코(EXCO), 부산의 벡스코(BEXCO), 광주의 김대중컨벤션센터(DJ Convention Center) 총 3개 컨벤션센터의 전반적인 현황과 시설, 조직구성, 행사개최, 경영수입 등 총체적인 운영현황을 분석하고, 수익성 창출 요인들을 담당 구성원들에게 설문조사를 통하여 직접 확인하고 이에 대한 면담조사를 통해 문제점과 개선방안을 찾아가는데 목적이 있다. 분석결과 인프라의 경우 교통여건, 관광자원, 산업인프라 순서로 중요도를 나타냈다. 행정기관의 경우 지방정부의 역할이 강조되었으며, 구성원의 경우 전문지식과 팀워크에서 중요도를 나타냈다. 면담조사에서는 지방컨벤션센터의 수익성 창출 및 활성화를 위해서는 수요가 공급을 창출하는 산업의 특성을 좀 더 이해하여 더 많은 투자가 있어야 하고, 구성원들의 근로환경, 복지수준, 교육훈련 등으로 직원의 직무만족도를 높이고 전문지식을 키울 수 있게 경영진들은 조직을 운용하여야 하며, 그 구성원들은 직원 간 협력과 구성원과의 좋은 팀워크로 수익성 창출에 기여하여야 함을 확인하였다. 또한 행정기관의 지속적인 지원 및 인프라 개선을 위해 앞으로 행정기관과 지방컨벤션센터의 유기적인 협조와 공동노력이 필요하다는 함의 점을 제시하였다. The purpose of this study is analyzing overall status and facilities, structure of organization, events holding, operating revenue of representing three local convention centers, EXCO in Daegu, BEXCO in Busan and DJ Convention Center in Kwangju, and directly identifying factors for the profitability through questionnaire to the members then finding out problems and improvements through the interviews with them. As a result of analysis, in case of infrastructure it shows the importance of traffic infrastructure, tour resources, and industrial infrastructure in order. In case of government agencies, it was emphasized the role of local governments and in the case of members the importance was appeared in expertise and teamwork. In interviews, for creating and revitalizing profitability of local convention center, more understanding about the characteristics of industry that demand creates supply, and more investment should be needed; to increase the job satisfaction of employees and develop their expertise the executives have to operate the organization with improving working environment, welfare, education and training; it has been identified that the members should contribute to create the profitability through the collaboration between members and good teamwork. Also, it suggested implications that continuing supports from government agencies and, needs of cooperations and joint efforts between government agencies and local convention centers.